Youth Empowerment Through Small Medium Micro Business Centers - Hedar, Fitria; Fitria Agustina, Isna (Universitas Muhammadiyah Sidoarjo, 2022)
Sidoarjo Regency is one of the districts that has potential in the field of home industry economics. One of them is located in Kedung Sumur Village, Krembung Subdistrict, Sidoarjo Regency in the form of a hawker village that has been established since 1961. Kedung Sumur Village Government has tried hard to be able to improve the economy of its people through the Kampung Jajanan UMKM program in hopes of being able to build an independent village in terms of its economy and also able to improve the welfare of its people. Thus the Kedung Sumur Village Government tried to deceive the community including its youth to be directly involved in the Kampung Jajanan UMKM program. The methods used qualitative descriptive data are obtained through observation, documentation, interviews and using the source of books, journals, and policy documents. The results of this study show that youth empowerment in realizing small and medium-sized micro business opportunities in the village of Kedung Sumur Village, Krembung District, Sidoarjo Regency has been running effectively. Seen from the three stages of empowerment that run well, namely the awareness stage in the form of socialization, the stage of ability transformation in the form of training and the stage of improving intellectual ability in the form of product innovation.